Carrion's disease - pathogenesis Test - Alzamora y Castro, Víctor V. (1940)
1. Is a Bartonella baciliformis rickettsioide germ - I endoteliotropo - and quite adapted to endocellular medium. In severe Bartonellosis. 2. Is intense colonization by endothelial cell system and the causal agent in parallel, therefore, proportional hemodifusión bloodstream by virus. 3. The causal relationship between CAV and Bartonella baciliformis Grave is difficult to explain if one ignores the action of toxic substances produced by the destruction of the virus. The reaction of the Host Cell progressively limits the number of parasites and work during this lag cell acute phase of the disease, clinically characterized by severe infectious, toxic state; pathologically degenerative lesions by particular anatomical hypertrophy, hyperplasia and myeloid mesenchymal reaction in the sector, the total number and breakdown of the blood picture appearance in the circulating blood of immature elements of all kinds. 4. Very often the acute illness is complicated by concurrent infection, usually caused by Salmonella, whose meaning is often decisive for the subject, which disfigures the anatomical table, modifies the body's response and aggravates infectious syndrome. 5. Bartonellosis Humana is an example of the immediate role the element plays in cell immunity. Anemia CARHTON, equivalents, warty eruption and latency are nothing but the expression of the existing current mode in virus-cell relationship.